Model of the impact of intangible resources on the competitiveness of listed companies from the WIGtech index in Poland - Perło, Dorota; Arszułowicz, Norbert (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The complexity of the phenomenon of competitiveness among contemporary enterprises implies the legitimacy of searching for sources of competitive advantages beyond traditional success factors. The concepts of enterprise competitiveness have evolved from classical economics to the present day and theories with a practical purpose such as: the theory of five forces by M.E. Porter and the theory of key competences by G. Hamel and C.K. Prahalad. Nowadays research on the phenomenon of the competitiveness of enterprises seeks answers to the following questions: what is the role of intangible resources in being competitive on the market and what types of intangible resources are the most important from the point of view of the research? Aim: The aim of the article is to examine the strength and direction of the impact of intangible resources on the competitiveness of listed companies. The article presents a theoretical model of the impact of intangible resources on the competitiveness of listed companies. The case study used for the empirical verification of the constructed model will be joint-stock companies from the Warsaw Stock Exchange selected according to the criteria defined in the article. Statistical data of the tested objects from 2021 will be implemented in the model in order to analyze its stability. Results: To achieve the aim of the article, the PLS-SEM method of modeling structural equations was used, which allows for the study of relationships between directly unobservable variables. The model consists of two parts: a structural (internal) model and a measurement (external) model. These models are also used in the parameter estimation process — they are interrelated. Two unobservable (hidden) variables were adopted in the constructed model: intangible resources (IR) and competitiveness of companies (CC). Hidden variables were defined based on a potential set of indicators (observable variables). The specification of the PLS-SEM model will make it possible to determine the strength and direction of the impact of intangible resources on the competitiveness of listed companies, based on the theory of key competences. Identification of the most important variables among intangible resources shaping the competitiveness of enterprises will contribute to the determination of theoretical conclusions and practical recommendations for listed companies in Poland.